Benzene exposure‐response and risk of lymphoid neoplasms in Chinese workers: A multicenter case‐cohort study. Issue 9 (31st May 2020) - Linet, Martha S.; Gilbert, Ethel S.; Vermeulen, Rudolf; Dores, Graça M.; Yin, Song‐Nian; Portengen, Lutzen; Hayes, Richard B.; Ji, Bu‐Tian; Lan, Qing; Li, Gui‐Lan; Rothman, Nathaniel
Abstract: Background: While international agreement supports a causal relationship of benzene exposure with acute myeloid leukemia, there is debate about benzene and lymphoid neoplasm risks. Methods: In a case‐cohort study with follow‐up of 110 631 Chinese workers during 1972‐1999, we evaluated benzene exposure‐response for non‐Hodgkin lymphoma (NHL), lymphoid leukemias (LL), acute lymphocytic leukemia (ALL), and total lymphoid neoplasms (LN). We estimated benzene exposures using state‐of‐the‐art hierarchical modeling of occupational factors calibrated with historical routine measurements and evaluated cumulative exposure‐response using Cox regression. Results: NHL and other specified LN were increased in exposed vs unexposed workers. However, there was no evidence of exposure‐response for NHL or other specified LN. Based on a linear exposure‐response, relative risks at 100 parts per million‐years (RR at 100 ppm‐years) for cumulative benzene exposure using a 2‐year lag (exposure at least 2 years before the time at risk) were 1.05 for NHL (95 percent confidence interval (CI) = 0.97, 1.27; 32 cases), 1.11 for LL (95% CI < 0, 1.66; 12 cases), 1.21 for ALL (95% CI < 0, 3.53; 10 cases), and 1.02 for total LN (95% CI < 0, 1.16; 49 cases). No statistically significant exposure‐response trends were apparent for these LN for 2 to <10‐year or ≥10‐year lags. NHL risks were not significantly modified by sex, age, or year at first exposure, attained age, or time since exposure. Conclusion: Given the study strengths and limitations, we found little evidence of exposure‐response for benzene and NHL, LL, ALL, or total LN, although NHL and other specified LN were increased in exposed vs unexposed individuals.